Exploring Types of Vocabulary Learning Strategies used by TESL Teacher Trainees at The Institute of Teachers Education - Omar, Umazah; Yaacob, Aizan (South Asian Journal of Social Sciences and Humanities, 2021)
Vocabulary is described as an essential element in second language learning. Having a good command over vocabulary helps in gaining unlimited access to latest information available at different platforms. Therefore, improving vocabulary through Vocabulary Learning Strategies (VLSs) will help the second language learners to become, academically and communicatively, more successful. The present study investigated the types of vocabulary learning strategies used by teacher trainees majoring in Teaching English as a Second Language (TESL) at the Institute for Teachers Education (ITEs) Darulaman Campus. Vocabulary learning strategies or skills are not directly taught to TESL teacher trainees during their training at ITEs. Teaching and learning vocabulary strategies are neglected by most of the teacher trainees. However, they need to make their teaching and learning processes more successful while learning a second language. This study was conducted based on the theories related to second language acquisition and used qualitative approach using the structured interviews of 14 TESL teacher trainees. The findings of the study were analysed based on Gu and Johnson’s (1996) and Schmitt (1996) categorisation of Vocabulary Learning Strategies and the results revealed TESL teacher trainees employed more metacognitive strategies in their vocabulary learning compared to other nine VLSs.